Industry Digital Maturities during Covid-19: Empirical Evidence from Indonesia - Afkar, Elvia; Syamsi, Rusi; Tamara, Dewi; Furinto, Asnan (ExcelingTech, 2020)
Abstract ‘Digital’ is becoming a more prevalent concept in current times and companies are competing in undergoing digitization in this Industry 4.0 era. The focus of this research is on measuring digital maturity of industries in Indonesia with the aim to find out which industry leading, and which lagging and to discover the impact of Covid-19 pandemic in Indonesia towards their digital maturity. This exploration is intended for companies to understand industry’s strengths that can be built on and which opportunities they may need to integrate to improve their digital maturity in the new normal. Methodology: The combination of Digital Maturity Model by Berghaus and Back and Digital Maturity Segment by Gill and VanBoskirk are used to measure digital maturities for the nine industries in Indonesia. Result: This study offers the information on the digital landscape across sectors before and during the pandemic and how each industry responds to the crisis as a result to its digital maturity. Conclusion: The study suggests that the landscape of digital maturities for all industries changed positively, with different magnitude for each industry, as the response to the Covid-19 pandemic. Further researches are recommended to find out the optimal balance in digital maturity for each industry and to explore the most impactful dimension of digital maturity per industry to its business outcome and sustainability.